Growth, development, and technological change - Volker Grossmann; Thomas M. Steger (Institute for the Study of Labor (IZA), 2007)
The theory of endogenous technical change has deeply contributed to our understanding of the fundamental sources of economic growth and development. In this chapter we survey important contributions in the field by focussing on the basic structure of endogenous growth models with horizontal as well as vertical innovation and emphasizing important implications for growth policy. We address issues like the scale effect problem, directed technological change to understand the evolution of wage inequality, long-run divergence between the innovating North and the imitating South due to inappropriate technology in the South, the relationship between trade and growth, competition and R&D, and the role of imperfect capital markets for R&D-based growth.
urn:nbn:de:101:1-20080425382
Keywords: 330; Neue Wachstumstheorie; Endogener technischer Fortschritt; Innovation; Innovationsdiffusion; Skalenertrag; Theorie